2020
DOI: 10.1080/00313831.2019.1705894
|View full text |Cite
|
Sign up to set email alerts
|

Quality of the Language-Learning Environment and Vocabulary Development in Early Childhood

Abstract: This study aims to enhance our knowledge of the associations between the quality of the language-learning environment in toddler childcare groups and children's vocabulary development from age 3 to age 5. Participants were 1,131 children (48% girls; age at T1 assessment: M = 35.5 months, SD = 2.7; age at T2 assessment: M = 60.3 months, SD = 1.4) from 206 toddler groups from 93 centres. Multilevel analysis showed that the quality of the language-learning environment experienced in toddler groups was associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 56 publications
3
14
0
2
Order By: Relevance
“…The current study showed that items related to oral language learning and interaction have high ECERS-3 scores. The results are consistent with other studies using the ECERS-3 (Early et al, 2018) and the Infant/toddler Environment Rating Scale (ITERS-R) (Bjørnestad & Os, 2018;Hansen & Broekhuizen, 2020), indicating that language development goals are and should be a great priority in preschool activities. Yet, the results in this study showed a positive correlation among the oral language items and items of Individualized teaching and Staff-child interactions included in the subscale Learning activities.…”
Section: Correlation Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…The current study showed that items related to oral language learning and interaction have high ECERS-3 scores. The results are consistent with other studies using the ECERS-3 (Early et al, 2018) and the Infant/toddler Environment Rating Scale (ITERS-R) (Bjørnestad & Os, 2018;Hansen & Broekhuizen, 2020), indicating that language development goals are and should be a great priority in preschool activities. Yet, the results in this study showed a positive correlation among the oral language items and items of Individualized teaching and Staff-child interactions included in the subscale Learning activities.…”
Section: Correlation Analysissupporting
confidence: 91%
“…Consequently, preschool teachers' competence to teach and create good conditions for children's learning becomes a critical aspect of preschool quality. A high-quality language learning environment is characterized by engaged and competent teachers who extend children's talk, facilitate dialogue and communication, and promote vocabulary development in everyday situations (Hansen & Broekhuizen, 2020). However, despite intentions in the Swedish preschool curriculum and widespread research, children's books are, for example, rarely used for teaching purposes or as a source for learning in Swedish preschools (Alatalo & Westlund, 2019;Sheridan et al, 2020).…”
Section: Theoretical Standpointsmentioning
confidence: 99%
“…Compared with children with parents, Chinese left-behind children feel more vulnerable, so teachers need to consider providing them with close attention and gentle care in preschools (Chang et al, 2019). In the absence of an effective and supportive home learning environment, well-organized classroom activities and effective support become more important attributes to increase the interaction opportunities between teachers and peers and, as a consequence, to improve children's vocabulary proficiency (Hansen and Broekhuizen, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, Hartman et al (2017) showed that there was a positive correlation between mothers' oral language ability and children's receptive language outcomes. More recently, Hansen and Broekhuizen (2020) found that the early childhood learning environment (i.e., early childhood centers and preschools), quality of staff interactions and conversation support had a significant influence on young children's language skills. According to a Chinese study (Hu et al, 2020), teachers' emotional support has a close relationship with the vocabulary of children from 3 to 5 years of age.…”
Section: Children's Vocabulary Development In the Early Yearsmentioning
confidence: 99%
“…Mengembangkan perkembangan bahasa anak melalui permainan sebaiknya dijelaskan secara struktur, dan penggunaan kalimat yang baik dan mudah dipahami oleh anak, khususnya mengingkatkan kosa kata anak. Kosa kata anak dapat meningkat jika pendidik atau orang tua menggunakan pembelajaran atau stimulasi yang tepat dan menarik bagi anak (Chen & Chan, 2019;Hansen & Broekhuizen, 2021). Salah satu stimulasi yang dapat dikembangkan melalui permainan tradisional (Junaedah et al, 2020;Pic et al, 2019).…”
Section: Gambar 3 Grafik Perbandingan Peningkatan Kosa Kata Pada Sikl...unclassified